Porphobilinogen Synthase : A Challenge for the Chemist ? - Stauffer, Frederic; Zizzari, Eleonora; Soldermann-Pissot, Carole; Faurite, Jean-Philippe; Neier, Reinhard (My University, 2001)
The initial steps in the biosynthesis of the tetrapyrrolic dyes, called the 'pigments of life', are highly convergent. The formation of porphobilinogen, the pyrrolic precursor of the tetrapyrrolic skeleton, uses δ-aminolevulinate as the starting material. This amino acid is dedicated to the biosynthesis of tetrapyrroles. However, the chemical condensation of δ-aminolevulinate leads to a symmetric pyrazine. Attempts to imitate the biosynthesis using one of the proposed pathways for the biosynthesis of porphobilinogen as a guideline has allowed us to synthesize a protected precursor of porphobilinogen in an efficient way. Based on the two major proposals for the biosynthesis, a series of specifically synthesized inhibitors was also tested. The inhibition behavior and the potency of the inhibitors expressed as their Ki value has unraveled an interesting relationship between the structure of the inhibitor and the strength of its interaction with the active site. The concerted use of mechanistic analysis, synthesis and kinetic studies of inhibitors has increased our knowledge about the enzyme porphobilinogen synthase. Structural studies of enzyme-inhibitor complexes will hopefully complement the kinetic results accumulated so far.
Keywords: δ-Aminolevulinate; Biosynthesis; Inhibition; Porphobilinogen; Tetrapyrroles